Absolute monocyte count predicts overall survival in mantle cell lymphomas: correlation with tumour‐associated macrophages. Issue 4 (29th October 2013) - Koh, Young Wha; Shin, Su‐Jin; Park, Chansik; Yoon, Dok Hyun; Suh, Cheolwon; Huh, Jooryung
Abstract Mantle cell lymphoma (MCL) is characterized by a variable clinical course in which patients can experience indolent disease or frequent relapses despite a good initial response to conventional therapy. Risk stratification of MCL is most frequently performed using the MCL International Prognostic Index (MIPI). Recent studies indicate that the peripheral blood absolute monocyte count (AMC) and tumour‐associated macrophages may reflect the state of the tumour microenvironment in lymphomas. The significance of AMC and tumour‐associated macrophages in the clinical course of MCL is unknown. The prognostic impact of the AMC, of CD68 expression and of CD163 expression was retrospectively examined in 103 MCL samples using the receiver operating characteristic curved. Patients with an AMC ≥ 375 cells/μL at diagnosis were more likely to present with advanced‐stage disease (p = 0.026), leukocytosis (p < 0.001), lymphocytosis (p = 0.01) and granulocytosis (p = 0.003). On univariate analysis, a high AMC (≥375 cells/μL) correlated with poorer overall survival (OS) (p = 0.01). Neither CD68 nor CD163 expression was significantly associated with either OS or event‐free survival. Multivariate analysis showed that a high AMC was a prognostic factor for OS, independent of the MIPI [hazards ratio (HR), 1.811; 95% confidence interval, 1.018–3.223; p = 0.043]. This study demonstrates that the AMC at the time of diagnosis is an independent prognostic factor for OS in MCL, which suggests the possibility that AMC may be used in addition to the MIPI to predict outcome in patients with MCL. Copyright © 2013 John Wiley & Sons, Ltd.